Evidence that chylomicron remnants and beta-VLDL are transported by the same receptor pathway in J774 murine macrophage-derived cells. - J L Ellsworth; A D Cooper; F B Kraemer (Journal of Lipid Research, 1990)
To characterize lipoprotein uptake by macrophages, we studied J774 murine macrophage-derived cells. Uptake of 125I-labeled beta-VLDL and 125I-labeled chylomicron remnants was saturable, specific, and of high affinity. Maximal specific uptake and the concentration at which half-maximal uptake occurred were similar for both beta-VLDL and chylomicron remnants. Specific uptake of 125I-labeled chylomicrons was only 1/5 that of the other two lipoproteins. Cholesterol loading decreased 125I-labeled chylomicron remnant and 125I-labeled beta-VLDL uptake by 25%. Chylomicron remnants and beta-VLDL were equipotent in cross-competition studies; acetyl-LDL did not compete, and human LDL was a poor competitor. Although the amounts of cell-associated lipoproteins were similar, beta-VLDL and chylomicron remnants had different effects on cellular lipid metabolism. beta-VLDL produced a threefold stimulation while chylomicron remnants caused a decrease in [3H]oleate incorporation into cholesteryl ester. beta-VLDL had no effect while chylomicron remnants caused a threefold increase in [3H]oleate incorporation into triacylglycerol. beta-VLDL produced a 44% suppression and chylomicron remnants produced a 78% increase in HMG-CoA reductase activity. In summary, J774 macrophages express a receptor site that recognizes both beta-VLDL and chylomicron remnants; however, these lipoproteins exhibit strikingly different effects on intracellular lipid metabolism.